Constipation Myths - Wendy J. Dahl (EDIS)
FSHN10-07, a 2-page illustrated fact sheet by Wendy J. Dahl, addresses the common myths about constipation. Includes references. Published by the UF Department of Food Science and Human Nutrition, July 2010.